THE EFFECT OF STEAMED PURPLE SWEET POTATOES ON BLOOD SUGAR LEVELS IN STUDENTS OF THE NUTRITION STUDY PROGRAM AT BINA MANDIRI UNIVERSITY, GORONTALO - Mantali, Sri Ayu; Warastuti, Rita Amini; Blongkod, Fitriani Rahmatismi (Journal of Health, Technology and Science (JHTS), 2026)
Sweet potato (Ipomoea batatas L.) is a tuber with many advantages compared to other tubers and is the fourth-largest source of carbohydrates in Indonesia, after rice, corn, and cassava. The high carbohydrate content of sweet potatoes makes them a good source of calories. The carbohydrate content in sweet potatoes is low on the glycemic index, meaning it does not significantly raise blood sugar levels when consumed. The purpose of this study is to determine the effect of steamed purple sweet potato on blood glucose levels in students. This research is an analytical experimental study with a quantitative approach using a one-group pretest-posttest design. The population and sample in this study consist of students, with a sample size of 35 respondents. The data used are primary and secondary, sourced from blood glucose tests conducted before and after the administration of steamed purple sweet potato. The data analysis includes univariate and bivariate analyses, descriptive tests, and the Wilcoxon rank test. Based on the research results, it was shown that the p-value = <.001 (p < 0.05), therefore (H0 is rejected), which means there is an effect of consuming steamed purple sweet potatoes on blood sugar levels in students. Steamed purple sweet potatoes tend not to significantly raise blood glucose levels in students due to their low glycemic index and high fiber content, which helps slow sugar absorption. However, excessive consumption can increase blood sugar levels due to the residual sugar.